The Tax Elasticity of Formal Work in Sub-Saharan African Countries - McKay, Andy; Pirttilä, Jukka; Schimanski, Caroline (Taylor & Francis, 2024)
Abstract When seeking to increase their tax revenues, policy makers face a likely tradeoff between decreasing personal income tax rates (making formalizing more attractive and potentially contributing to revenue) and alternatively raising tax rates (potentially slowing down the formalization of the economy if people prefer informal employment). Evidence on formal versus informal earnings and job characteristics in different sectors is limited in African countries, and in particular very little is known about the impact of tax changes on the extent of informality. This paper therefore estimates the personal income tax responsiveness of the extensive margin of formality, i.e. the propensity to be a formal as opposed to an informal worker, for Ghana, Rwanda, Tanzania, and Uganda, using repeated cross-sections of household data and applying grouping estimator techniques. Perhaps because of labour demand constraints and other frictions, the paper finds non-significant relations between the formal employment share and the formal-informal earnings differences.
Keywords: Developing countries; Sub-Saharan Africa; taxation; labour supply; informality